IDENTITY POLITICS WITHIN TRIBE IN VILLAGE GOVERNMENTS HEAD ELECTION: A case study in Wederok Village, Malaka Regency, East Nusa Tenggara - Alfirdaus, Laila; Bria, Fridus (CosmoGov: Jurnal Ilmu Pemerintahan, 2020)
This article discusses identity politics in the village head election level. Studies on identity politics so far are mostly focused on elections in a government system that is in a higher concentration than a village, as in legislature and presidential elections. Attention to a similar issue in the village level is less to exist, partly because the community is generally assumed to be homogeneous. Meanwhile, in the village level, people remain plural, moreover in villages that live outside Java, where the number of tribes within communities is many. This is not to mention newcomers from the other islands. Using a case study in the Election of Village Heads in Wederok Village, Weliman Sub-district, Malacca District, East Nusa Tenggara, this research found that identity politics in village government head election play a crucial role as in the other elections, as legislature and regency head elections, even in the same tribe in the same village. This article is based on qualitative research with in-depth interviews as main data collection methods. The results showed that in the election of Wederok village head, people become divided into particular parts, mostly based on sub-tribe (kinship). The village head election involved candidates from the different tribal identities, despite the connection between them because of inter-tribe marriage. Tribe-based competition in the village head level in Wederok even led to further conflict, which needs for reconciliation. gb777